ẢNH HƯỞNG CỦA TIỀN CHẤT ĐẾN QUÁ TRÌNH TỔNG HỢP VẬT LIỆU MAO QUẢN TRUNG BÌNH MgO - Huyền, Phạm Thanh; Lam, Ngô Lê; Chinh, Nguyễn Huy; Chính, Huỳnh Đăng (Vietnam Journal of Chemistry, 2012)
Mesoporous MgO has been synthesized with different precursors and the present of F127 as soft template which is completely removed by soxhlet. Characterizations of synthesized materials and phenomena happened during synthesis were studied by TG-MS, BET, SEM. The results show that mesoporous MgO synthesized from magnesium nitrate has higher surface area and pore volume than that synthesized from magnesium acetate.